Description of the larva of Hypsilara (Coleoptera: Elmidae) - Laššová, Kristína; Čiamporová-Zaťovičová, Zuzana; Jr, Fedor Čiampor (Zootaxa, 2023)
The mature larva of the Larainae riffle beetle genus Hypsilara Maier & Spangler, 2011 is described here for the first time, based on larvae of Hypsilara autanai Laššová, Čiampor Jr, Čiamporová-Zaťovičová, 2014. The larvae were collected with adults in the stream near the tepui Cerro Autana and Cerro Cuao (southwestern Venezuela) and associated together using DNA barcoding. Larvae of Hypsilara strongly resemble those of Phanoceroides, here we present important morphological diagnostic characters. This description complements the descriptions of the Larainae larvae in the Neotropics, as the larva of Hypsilara was the last one of the group missing so far.